2022
DOI: 10.1002/hipo.23415
|View full text |Cite
|
Sign up to set email alerts
|

Activin A regulates the excitability of hippocampal mossy cells

Abstract: Mossy cells (MCs) in the hilus of the dentate gyrus (DG) receive increasing attention as a major player controlling information processing in the DG network. Furthermore, disturbed MC activity has been implicated in widespread neuropsychiatric disorders such as epilepsy and major depression. Using whole‐cell patch‐clamp recordings from MCs in acute hippocampal slices from wild type and transgenic mice, we demonstrate that activin, a member of the transforming growth factor‐β (TGF‐β) family, has a strong neurom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Nevertheless, the question remains whether the electrophysiological effects observed in adult dnActRIB neurons are a direct consequence of the lack of activin receptor signaling or rather reflects adaptive changes over time. In a previous study on (glutamatergic) mossy cells in the hilus of the dentate gyrus, 41 we found that administration of recombinant activin A to wild-type neurons produced electrophysiological effects exactly opposite to those observed in dnActRIB neurons. It is therefore plausible to assume that the altered excitability of mutant mossy cells and, by analogy, of the mutant CA1 pyramidal cells examined here, arose directly from disrupted activin receptor signaling.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Nevertheless, the question remains whether the electrophysiological effects observed in adult dnActRIB neurons are a direct consequence of the lack of activin receptor signaling or rather reflects adaptive changes over time. In a previous study on (glutamatergic) mossy cells in the hilus of the dentate gyrus, 41 we found that administration of recombinant activin A to wild-type neurons produced electrophysiological effects exactly opposite to those observed in dnActRIB neurons. It is therefore plausible to assume that the altered excitability of mutant mossy cells and, by analogy, of the mutant CA1 pyramidal cells examined here, arose directly from disrupted activin receptor signaling.…”
Section: Discussionmentioning
confidence: 53%
“…Of note, hilar interneurons, which are not supposed to express the transgene, also showed changes in their firing properties when measured in slices from dnActRIB mice. 41 Thus, elimination of endogenous activin signaling in one cell type may entail adaptive changes in other neurons of the hippocampal network.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns that the enhanced excitability of GC after EE would affect sparse coding in the dentate gyrus might be dispelled by our observation that a rise in activin A produces also an excitatory effect in mossy cells of the hilus (Schmidt et al, 2022 ). Mossy cells are glutamatergic neurons, which are excited by collaterals of GC axons (mossy fibers).…”
Section: Discussionmentioning
confidence: 95%